Implementing design thinking in organizations: An exploratory study - David Dunne (Journal of Organization Design, 2018)
Design thinking has been adopted by organizations in all sectors of the economy. In this qualitative study, I explore organizations' goals in adopting design thinking, the challenges such programs encounter, and the approaches they have taken to deal with these challenges. I find that unclear goals, the need to build legitimacy, cultural resistance, and leadership turnover can compromise the work of design programs. Possible antidotes include technological and collaborative platforms, and extending design thinking into the implementation process.
Keywords: 650; Design thinking; Innovation; Organization design; Organizational culture